INTERKALASI TETRAETIL ORTOSILIKAT (TEOS) PADA LEMPUNG TERAKTIFASI ASAM SULFAT DAN PEMANFAATANNYA SEBAGAI ADSORBEN WARNA LIMBAH GARMEN - Suarya, P.; Bawa Putra, A. A.; Wisudawan, Devi (Jurnal Kimia (Journal of Chemistry), 2012)
Interchalation of Tetraethyl orthosilicate (TEOS) with acid activated clay has been studied. As for characterization of the modified clay. Acid-base titration methode was used to determine the surface acidity. Methylen blue method was used to determine the surface area while spectrophotometer UV-Vis was used to determine the amount of dye adsorbted by the modified clay. The results showed that activation of clay with sulphuric acid and interchalat ion with TEOS increased the surface acidity of the clay. The value of surface acidity of S0-0(without activation); Sa-0(interchalated with TEOS 0%); Sa-5 (interchalated with TEOS 5%); Sa-10(interchalated with TEOS 10%); Sa-15 (interchalated with TEOS 15%) were 0.5064; 0.8733; 0.8486; 1.0005; and 0.8926 mmol/gadsorbent respectively. The specific surface area of S0-0; Sa-0; Sa-5; Sa-10; Sa-15 were27.2391 m2/g; 28.4019 m2/g; 28.2767 m2/g; 29.2220; m2/g dan 29.1621 m2/g, respectively. Further more, it was shown that, acid actived clay interchalated with 10% TEOS was the best adsorbent which adsorbed 83,64% of the dye indicated by the change of the colour from dark yellow to light yellow.
Keywords: clay, adsorbent, garment colour, adsorption, Tetraethyl orthosilicate